The Mediating Effects of Digital HR Practices on Competitive Advantage in Shariah-Compliant Banks in Indonesia - Rini Ardista; Asep Nur Imam Munandar (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The rapid growth of digital transformation is reshaping how organizations, especially Islamic banks, manage their human resources to maintain competitiveness in a changing market. This study aims to explore how managerial behavior, employee empowerment, and strategic human resource facilitation impact competitive advantage, with digital human resource practices acting as a mediator in Indonesian Islamic banks. A quantitative approach was used, involving a survey of 289 employees from 14 Islamic banks in the Jabodetabek area and West Java, analyzed through Structural Equation Modeling. The findings indicate that employee empowerment and digital human resource practices significantly enhance competitive advantage, with digital practices mediating the effects of empowerment and strategic facilitation. However, managerial behavior showed a limited direct influence, and strategic facilitation did not significantly affect competitive advantage directly. The conclusion suggests that Islamic banks should prioritize employee empowerment and invest in digital human resource systems to strengthen their market position, while addressing challenges like digital literacy and regional limitations. These insights offer valuable guidance for human resource strategies aligned with Islamic values and principles.